2018
DOI: 10.12938/bmfh.17-021
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of murine cell-mediated immunity by dietary administration of a cell preparation of <i>Enterococcus faecalis</i> strain KH-2 and its possible activity against tumour development in mice

Abstract: It is well known that dietary lactic acid bacteria (LAB) stimulate cell-mediated immunity such as natural killer (NK) activity in mice. Here, we aimed to assay the immunomodulatory effects of a cell preparation of Enterococcus faecalis strain KH-2 (CPEF). We further evaluated the possibility of antitumour activity caused by CPEF administration, because NK cells actively participate in the prevention of tumour formation. NK cell activity and gene expression of IFN-γ and Perforin 1, which were induced most likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Although it remains to be elucidated how the administration of Enterococcus spp. affects the process of wound-healing in skin, treatment with heat-killed E. faecalis strains EC-12 and KH2 was reported to induce the production of inflammatory cytokines by macrophages and to activate natural killer (NK) cells and cytotoxic T cells, respectively [ 13 , 14 ]. In addition, several studies revealed that LAB promote leukocyte function and increase the production of VEGF, one of the most important mediators of angiogenesis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it remains to be elucidated how the administration of Enterococcus spp. affects the process of wound-healing in skin, treatment with heat-killed E. faecalis strains EC-12 and KH2 was reported to induce the production of inflammatory cytokines by macrophages and to activate natural killer (NK) cells and cytotoxic T cells, respectively [ 13 , 14 ]. In addition, several studies revealed that LAB promote leukocyte function and increase the production of VEGF, one of the most important mediators of angiogenesis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus is a large genus of health-promoting lactic acid bacteria that are common commensals in the human gut. Oral administration of a cell preparation of Enterococcus faecalis strain KH-2 improved the survival rate of Meth-A fibrosarcoma-bearing mice via stimulation of an immune response in splenocytes, which involved systemic cellular immunity processes such as cytotoxic activity and active T cells (Tsukahara et al, 2018). In addition, isoliquiritigenin, a flavonoid isolated from a related species (Glycyrrhiza glabra L.), has also shown antitumor efficacy.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Lactic acid bacteria (LAB) intake has several major health benefits, such as improvement of fecal microbiota [ 1 , 2 , 3 ] and antibacterial [ 4 , 5 ], anti-allergy [ 6 , 7 ], antitumor [ 8 , 9 ], and antiviral effects [ 10 , 11 , 12 ]. Bacterial cell walls [ 13 ] and extracellular polysaccharides produced by bacteria [ 14 ] have been reported as factors affecting the immune stimulation and biological defense provided by LAB, but no active component has yet been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%